Predictors of Thrombus Dissolution in the Left Atrial Appendage in Patients with Persistent Nonvalvular Atrial Fibrillation - E. S. Mazur; V. V. Mazur; N. D. Bazhenov; Yu. A. Orlov (SINAPS LLC, 2022)
The aim of this study is to identify factors influencing the likelihood of the thrombus dissolution in the left atrial appendage in patients with persistent nonvalvular atrial fibrillation. Material and methods. A repeated transesophageal echocardiography was performed in 88 patients with persistent nonvalvular atrial fibrillation and with the left atrial appendage thrombus at the first transesophageal echocardiography. Results. The second transesophageal echocardiography was performed on average 30.0 (22.0; 40.0) days after the first one, the thrombus dissolution in the left atrial appendage was revealed in 60 (68.2%) patients. The multivariate logistic regression analysis showed that the chances of the thrombus dissolution increased by 5.789 (1.907-17.568) times with the thrombus size not more 25 mm, by 5.318 (1.325-21.353) times with the left atrial appendage emptying flow velocity not less 20 cm/s and 3.687 (1.229-11.059) times when prescribing the direct oral anticoagulants, and not warfarin. Combination of two or more factors give the probability of the thrombus dissolution of more than 89.6%. Conclusion. The probability of the thrombus dissolution in left atrial appendage in patients with persistent nonvalvular atrial fibrillation increases with a small thrombus size, a high the left atrial appendage emptying flow velocity, and if direct oral anticoagulants were prescribed.